Multi-Layered Hydrogels for Biomedical Applications - Liu, Guiting; Ding, Zhangfan; Yuan, Qijuan; Xie, Huixu; Gu, Zhipeng (Frontiers in Chemistry, 2018)
Multi-layered hydrogels with organization of various functional layers have been the materials of choice for biomedical applications. This review summarized the recent progress of multi-layered hydrogels according to their preparation methods: layer-by-layer self-assembly technology, step-wise technique, photo-polymerization technique and sequential electrospinning technique. In addition, their morphology and biomedical applications were also introduced. At the end of this review, we discussed the current challenges to the development of multi-layered hydrogels and pointed out that 3D printing may provide a new platform for the design of multi-layered hydrogels and expand their applications in the biomedical field.